2022
DOI: 10.1093/mnras/stac2596
|View full text |Cite
|
Sign up to set email alerts
|

Repeating fast radio bursts with high burst rates by plate collisions in neutron star crusts

Abstract: Some repeating fast radio burst (FRB) sources show high burst rates, and the physical origin is still unknown. Outstandingly, the first repeater FRB 121102 appears extremely high burst rate with the maximum value reaching 122 h−1 or even higher. In this work, we propose that the high burst rate of an FRB repeater may be due to plate collisions in the crust of young neutron stars (NSs). In the crust of an NS, vortex lines are pinned to the lattice nuclei. When the relative angular velocity between the superflui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 123 publications
1
6
0
Order By: Relevance
“…In the framework of the magnetar model, zones of magnetic stress are generated in the crust due to magnetic field evolution and field reconfiguration through Hall drift and ohmic dissipation (Ruderman et al 1998). When the magnetic stresses exceed a critical threshold, frequent crustal fractures will occur, which can produce repeating FRBs (Suvorov & Kokkotas 2019;Lu et al 2020;Li et al 2022). In fracture processes, the crustal strain redistributes through neighbor tectonic interactions, which can trigger subsequent bursts.…”
Section: Discussionmentioning
confidence: 99%
“…In the framework of the magnetar model, zones of magnetic stress are generated in the crust due to magnetic field evolution and field reconfiguration through Hall drift and ohmic dissipation (Ruderman et al 1998). When the magnetic stresses exceed a critical threshold, frequent crustal fractures will occur, which can produce repeating FRBs (Suvorov & Kokkotas 2019;Lu et al 2020;Li et al 2022). In fracture processes, the crustal strain redistributes through neighbor tectonic interactions, which can trigger subsequent bursts.…”
Section: Discussionmentioning
confidence: 99%
“…After the glitch, the motion of the core superfluid neutron vortices in the direction perpendicular to the spin axis during the spin-down relaxation phase of the glitch would alter the core magnetic field, which would result in the movement of the neutron star crust and the change in the surface magnetic field (Ruderman et al 1998). Crustquakes are expected if the solid crust does not plastically adjust to the less-oblate equilibrium shape required by the pulsar's spin-down or if the magnetic stress exceeds the shear modulus (Baym & Pines 1971;Thompson & Duncan 1995;Perna & Pons 2011;Li et al 2022). Crustal fracturing produces Alfvén waves and then generates X-ray bursts (Thompson & Duncan 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism triggering FRB 200428 is not well understood yet. It is widely suggested that FRBs are generated by the magnetospheric activities of magnetars, either triggered internally (Yang & Zhang 2018;Lyubarsky 2020a;Lu et al 2020;Yang & Zhang 2021;Wang et al 2021;Li et al 2022) or externally (Zhang 2017Geng et al 2021;Dai 2020). Recently, Younes et al (2022) report that SGR J1935+2154 experienced one spin-down glitch, followed by FRB-like bursts and a pulsed radio episode.…”
mentioning
confidence: 99%
“…In the framework of the magnetar model, zones of magnetic stress are generated in the crust due to magnetic field evolution and field reconfiguration through Hall drift and Ohmic dissipation (Ruderman et al 1998). When the magnetic stresses exceed a critical threshold, frequent crustal fractures will occur, which can produce repeating FRBs (Suvorov & Kokkotas 2019;Lu et al 2020;Li et al 2022). In fracture processes, the crustal strain redistributes through neighbour tectonic interactions, which can trigger subsequent bursts.…”
Section: Discussionmentioning
confidence: 99%
“…One possible trigger mechanism is the crustal failure of a neutron star, favoring emission from the stellar magnetosphere (Suvorov & Kokkotas 2019;Lu et al 2020;Li et al 2022). FRB 20201124A…”
Section: Discussionmentioning
confidence: 99%